High-Quality, High-Throughput, Early Whole-Body Bone Scanning - Ell, P. J.; Al-Eid, M. A.; Lui, D.; Pearce, P. C.; Elliott, A. T.; Brown, N. J. G. (Nuklearmedizin - NuclearMedicine, 1977)
99m Tc-IDP allows for high-quality, high-throughput and early whole-body bone scanning. Whole-body bone scans obtained at 30 min after intravenous administration of the tracer were compared with the standard and delayed 180 min p. i. images. A subtraction technique allowed for the analysis of the 30 min scans and it was found that in both types of investigation the same clinical information was present. This procedure will therefore increase considerably the throughput of whole-body bone scans in a busy department of nuclear medicine. It is however inadequate for detailed analysis of the skeleton (evaluation of benign bone disease).